Impact of skill mismatch on employee job satisfaction. A study on HRM downstream corporate office Petronas / Nur Sabrina Suhaimi - Suhaimi, Nur Sabrina (Faculty of Business and Management, 2014)
The purpose of this study is to identify to what extend the type of skill mismatch impact on employee job satisfaction. The dependent variable is Job Satisfaction and independent variable are Over Skilled and Under Skilled which is among the type of skill mismatch. This research is being conducted in HRM Downstream Corporate Office, PETRONAS. In completing this research, about 48 questionnaires have been distributed to the respondents. The respondents is pick randomly among the staff in HRM Downstream Corporate Office, PETRONAS. In order to get the result, the researcher has used SPSS program to analyze data from the information gathered. From the findings, the researcher indicates that there is a relationship between the type of skill mismatch and employee job satisfaction.